PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN HOMESCHOOLING KAK SETO DI SURAKARTA YANG DIMODERASI BUDAYA ORGANISASI - Dwi Wijaya, Suprayitno & Sutarno (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2016)
This study aims to (1) analyze the significance of the effect of compensation to employee performance Homeschooling Kak Seto in Surakarta. (2) analyze the significance of the influence of labor discipline on employee performance Homeschooling Kak Seto in Surakarta (3) analyze the significance of the influence of organizational culture on employee performance Homeschooling Kak Seto in Surakarta (4) analyze the significance of the effect of compensation to employee performance homeschooling kak seto in Surakarta moderated by organizational culture (5) to analyze the significance of the influence of labor discipline on employee performance Homeschooling Kak Seto in Surakarta moderated by the organization's culture. The population in this study are employees Homeschooling Kak Seto in Surakarta totaling 30 people, test instrument using validity and reliability test. Classic assumption test using the test: multicollinearity, heteroscedasticity, autocorrelation and normality. Data analysis technique used is multiple linear regression analysis, t-test, F, coefficient determination and test the absolute difference. Based on the validity of the test showed that all valid instrument and of the reliability test showed all instruments reliable. Classic assumption test results show that the variable data of this study has been to meet the assumptions required by multiple linear regression model that does not happen multikolinearitas problem, does not occur heteroskedastisitas, and autocorrelation, and residual normal. The conclusion of this study are that: (1) compensation no significant effect on the performance of employees (2) discipline of work have a significant effect on the performance of employees, (3) organizational culture significantly influence employee performance, (4) the organizational culture does not moderate the influence of compensation on performance, (5) does not moderate the influence of organizational culture on employee performance work discipline.Keywords: compensation, work discipline, organizational culture, employee performance.